COULD NATION-STATE HAVE A FUTURE? - Зайдель, М.І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The article deals with a place and a role of nation-state in global policy. The author focuses on the problems that the nation-state conflicts with. The main attention is given for the national sovereignty’s transformation in process of globalization. The nation-states aren’t disappeared today, they are the most universal and steady elements of modern civilization. It is presented arguments that the sovereignty of state are partly collapsed and that is not mean a disappearance of the nation-state.